Concomitant mutations and splice variants in KRAS and BRAF demonstrate complex perturbation of the Ras/Raf signalling pathway in advanced colorectal cancer. Issue 9 (26th May 2009) - Seth, R; Crook, S; Ibrahem, S; Fadhil, W; Jackson, D; Ilyas, M
Abstract : Background and aims: KRAS and BRAF mutations occur in colorectal cancers (CRCs) and are considered mutually exclusive methods of activating the RAS/RAF/MEK/ERK pathway. This pathway is a therapeutic target and KRAS mutation may predict tumour responsiveness. The purpose of this study was to investigate the relationship between KRAS and BRAF mutations in 24 CRC cell lines and 29 advanced CRCs. Methods: KRAS and BRAF mutations were detected using high resolution melting and sequencing. Expression of mutations was confirmed by reverse transcription- PCR (RT-PCR) and sequencing. CpG island methylator phenotype (CIMP) was tested by methylation-specific PCR. Results: KRAS or BRAF mutation occurred in 79% of cell lines and 59% of CRCs. In the cell lines, KRAS mutations occurred in 54% of cases (with 62% in codons 12/13 and 38% in other codons). Four cell lines had a homozygous mutation. Only heterozygous BRAF mutations were detected in 29% cell lines. The V600E mutation occurred most commonly and was associated with CIMP+ status (p = 0.005). Mutations at codons 529 and 581 were also found and, in one case, BRAF and KRAS mutation co-occurred. Unexpectedly, BRAF splice variants (with a predicted kinase-dead protein) were found in 5/24 (21%) cell lines. In advanced CRCs, KRAS mutations occurred in 48% of cases (64% codons 12/13, 36% other codons) and BRAF mutations in 10% (66% V600E, 33% exon 11). A compound KRAS/BRAF mutation was not seen. Conclusions: Disrupted Ras/Raf signalling is common in CRC. Homozygous KRAS mutations and concomitant KRAS/BRAF mutations may be indicative of a gene dosage effect. The significance of BRAF splice variants is uncertain but may represent another layer of complexity. Finally, if KRAS mutation is to be used for predictive testing, then the whole gene may need to be screened as mutations occur outside codons 12/13.